Endothelin-1 concentration is increased in the aqueous humour of patients with exfoliation syndrome. Issue 4 (18th March 2004) - Koliakos, G G; Konstas, A G P; Schlötzer-Schrehardt, U; Hollo, G; Mitova, D; Kovatchev, D; Maloutas, S; Georgiadis, N
Abstract : Background/aim: Endothelin 1 (ET-1) is considered the most potent vasoconstrictor in the body and the eye. This molecule may play a significant role in the pathobiology of exfoliation syndrome (XFS), a disorder characterised by a progressive iris vasculopathy. The purpose of this study was to investigate the concentration of ET-1 in the aqueous humour of cataract patients with and without XFS. Methods: Aqueous humour samples were obtained from 25 consecutive eyes of 25 cataract patients with XFS and an equal number of age matched controls during phacoemulsification cataract surgery. None of the subjects had elevated intraocular pressure or glaucoma. ET-1 concentration in the aqueous was measured using a specific immunoassay with 100% immunoreactivity for ET-1. Total aqueous humour protein concentration was measured with a microplate Coomassie blue based method and was correlated with ET-1 concentration. Results: Mean ET-1 concentration in the XFS aqueous samples (4.6 (SD 2.3) pg/ml) was significantly higher than that measured in the age matched control samples (2.8 (SD 1.71) pg/ml); (p = 0.006). Although total protein concentration was significantly elevated in the XFS samples (0.380 (SD 0.159) v 0.279 (SD 0.144) mg/ml in the controls); (p = 0.023), no correlation was found between aqueous ET-1 and total protein concentration (p = 0.730). Conclusion: The increased concentration of ET-1 in the aqueous humour of XFS patients suggests that ET-1 may play a role in the pathobiology of XFS.